Fingerroot (Boesenbergia pandurata) : A Prospective Anticancer Therapy - Marsya Yonna Nurrachma; Hilyatul Fadliyah; Edy Meiyanto (Indonesian Society for Cancer Chemoprevention, 2018)
Beside as a spice in Indonesian cooking, Fingerroot (Boesenbergia pandurata) regularly is used as a mixture of herbal medicine. Scientifically, the phytochemical content of the fingerroot rhizome showed some therapeutical effects such as antibacterial, anti-inflammatory, anti or pro-oxidant, and also anticancer. In this article, we summarize some studies especially about anticancer activity of fingerroot and its constituent coumpound. We found that fingerroot is capable of inhibiting various pathways of cell physiology processes. One potential pathway to be inhibited by fingerroot is Poly (ADP-ribose) polymerase (PARP) which has role in apoptotic induction. In the future, it is necessary to purify the extract to obtain maximum efficacy and also formulation studies of fingerroot will be interesting to do to.Keywords : fingerroot, anti-cancer, chemopreventive, herbal medicineBeside as a spice in Indonesian cooking, Fingerroot (Boesenbergia pandurata)regularly is used as a mixture of herbal medicine. Scientifically, the phytochemical contentof the fingerroot rhizome showed some therapeutical effects such as antibacterial, antiinflammatory,anti or pro-oxidant, and also anticancer. In this article, we summarizesome studies especially about anticancer activity of fingerroot and its constituentcoumpound. We found that fingerroot is capable of inhibiting various pathways of cellphysiology processes. One potential pathway to be inhibited by fingerroot is Poly (ADPribose)polymerase (PARP) which has role in apoptotic induction. In the future, it isnecessary to purify the extract to obtain maximum efficacy and also formulation studiesof fingerroot will be interesting to do to.